1991
DOI: 10.1136/gut.32.11.1355
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive and motor components of the antidiarrhoeal action of loperamide: an in vivo study in pigs.

Abstract: The effects of loperamide (0.1 mg/kg orally) on net colonic water absorption, orocolonic transit time, and intestinal motility were investigated in pigs chronically fitted either with two cannulas in the proximal colon and a catheter in the duodenum and the ileum or with intraparietal electrodes on the duodenum, jejunum, caecum, and proximal colon and a duodenal catheter. Loperamide, given 20 minutes before a meal reduced significantly colonic net water absorption for 10 hours after eating. It also reduced col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Thus, zingerone seems to be beneficial for patients with colonic disorder related to hyperexcitability of smooth muscles. In support of this notion, it has been reported that some antidiarrheal drugs, such as loperamide and wood creosote, possess inhibitory effects on gut motility in addition to their modulatory effects on fluid absorption/secretion [30][31][32][33][34]. These agents can act directly on intestinal smooth muscles [35,36], being consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, zingerone seems to be beneficial for patients with colonic disorder related to hyperexcitability of smooth muscles. In support of this notion, it has been reported that some antidiarrheal drugs, such as loperamide and wood creosote, possess inhibitory effects on gut motility in addition to their modulatory effects on fluid absorption/secretion [30][31][32][33][34]. These agents can act directly on intestinal smooth muscles [35,36], being consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Loperamide, a standard antidiarrheal drug is also reported have no effect on colonic motility and incline to slowdown small intestinal transit, reduced colonic rate of flow, and consequently increased colonic water absorption (Theoderau, 1991). EtAI extract also significantly decreased intestinal transit as observed by the decrease in transit motility of charcoal meal.…”
Section: Acute Toxicity Studiesmentioning
confidence: 99%
“…of endogenous prostaglandin (Galvez et al, 1993). Loperamide, apart from regulating the gastrointestinal tract, is also reported to slow down transit in the small intestine, reduce colon fl ow rate, and consequently any effect on colonic motility (Theoderau et al, 1991;Salgado et al, 2005). In this study, the hydroethanolic extract of A. cadamba displayed a signifi cant and dose-dependent antidiarrhoeal property.…”
Section: Resultsmentioning
confidence: 71%